PARTISIPASI MASYARAKAT DALAM PENGELOLAAN BADAN USAHA MILIK DESA (BUMDES) JAYA TIRTA DESA GEDONGARUM KECAMATAN KANOR KABUPATEN BOJONEGORO - Galih Wahyu Pradana; Ely Rismanita (Universitas Negeri Surabaya, 2022)
BUMDes is a form of community participation in village development, because BUMDes is formed on the initiative and participation of village communities. BUMDes Jaya Tirta is present in the midst of the Gedongarum Village community as a provider of pumping services, rice milling and drug stores. The presence of BUMDes Jaya Tirta has proven to be able to boost the economy of Gedongarum Village. But behind its success, the existence of the community is less involved in the management of BUMDes Jaya Tirta. Therefore, the purpose of this study is to analyze the forms of participation of the Gedongarum community in BUMDes Jaya Tirta. This study uses a descriptive research design with a qualitative approach. With the focus of the research, namely analyzing the forms of community participation in the management of BUMDes Jaya Tirta. As an analytical tool in this study, researchers used the theory according to Cohen and Uphoff quoted in (Dwiningrum, 2011: 61-63), including: a). Participation in decision making b). Participation in implementation c). Participation in benefit-taking, and d). Participation in evaluation. The results showed that, in making decisions, the community was still less active in participating. In the implementation, the community has participated well in providing labor and material. However, in its management, community participation is still limited. In taking benefits, the community can feel it both in terms of qualitative and quantitative, but when viewed from the economic side of the community, the existence of BUMDes has not provided significant benefits for the community itself. In the evaluation, the community can participate well. The suggestions given by the researchers include creating non-formal forums to stimulate the community to want to express their aspirations, providing understanding to the community regarding the importance of community participation in decision making, adding new business units and involving the community more in managing BUMDes directly. Keywords: Community Participation, Village Owned Enterprises (BUMDes), Jaya Tirta.